Incidental gastrointestinal 18F-Fluorodeoxyglucose uptake associated with lung cancer. Issue 1 (December 2015) - Vella-Boucaud, Juliette; Papathanassiou, Dimitri; Bouche, Olivier; Prevost, Alain; Lestra, Thibault; Dury, Sandra; Vallerand, Hervé; Perotin, Jeanne-Marie; Launois, Claire; Boissiere, Louis; Brasseur, Mathilde; Lebargy, François; et al.
Abstract Background F-Fluorodeoxyglucose positron emission tomography/computed tomography (18 F-FDG PET/CT) is increasingly used for the initial staging and restaging of lung cancer. Incidental gastrointestinal findings are often observed on18 F-FDG PET/CT. The objective of this study was to assess incidental18 F-FDG uptake by the gastrointestinal tract (GIT) in patients with lung cancer. Methods Two hundred thirty consecutive18 F-FDG PET/CT examinations performed for lung cancer over a 3-year period were retrospectively reviewed for the presence of incidental FDG uptake in the GIT. The charts of patients with positive FDG uptake were then reviewed and analysed to determine the GIT uptake sites, the standardized uptake value (SUV) max and the final clinical diagnosis. Results Fifty-two patients (52/230, 23 %) demonstrated incidental FDG uptake in the GIT. Thirty-three patients (63.5 %) had diffuse uptake (oesophagus, n = 2, colon, n = 31) and 19 patients (36.5 %) had focal uptake (oesophagus, n = 1, small bowel, n = 1, ascending colon, n = 5, descending colon, n = 4, sigmoid, n = 4, rectum, n = 3, and anal margin, n = 1). Twelve of the 52 patients with GIT uptake were further investigated, revealing, a diagnosis of malignancy in 4 patients with focal FDG uptake. No significant differences in mean SUVmax were observed between patients with malignant and benign GIT diseases. Conclusion This study demonstrates a high incidence of FDG uptake in the GIT associated with lung cancer. Focal GIT uptake was frequently associated with malignant disease. These results suggest that further GIT investigations should be performed in patients with focal GIT uptake.